PRACTICE OF PRODUCTION OF POLYCOMPONENT THREAS FROM A MIXTURE OF NATURAL AND CHEMICAL FIBERS - Erkinov, Zokirjon; Dadadzhonov , Sharabidin; Akhunbabaev , Okhunzhon; Muxamadrasulov , Shamsiddin; Akhunbabaev , Ulugbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article presents the results of the practice of producing poly-component threads from a mixture of natural and chemical fibers in the production conditions of spinning factories and the production of fabrics and knitted products from them in weaving and knitting enterprises using the technology created at the Uzbek Research Institute of Natural Fibers. The mixtures of polycomponent threads used silk wool from fibrous waste of natural silk, cotton, wool and chemical fibers in the form of viscose, polyester fibers, as well as lycra. From the obtained polycomponent threads, suit and dress fabrics are produced at weaving enterprises, as well as women's knitwear at knitting enterprises. As a result of experimental studies, recommendations have been developed for the production of multicomponent threads and fabrics and knitted products from them in the production conditions of enterprises.